A Phenomenological Study of The Implementation of Indonesian Language Learning During the Covid-19 Pandemic - Pauzia, Resti; Fatmawati (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2023)
This research was motivated by a number of phenomena that occurred in the implementation of online learning at SMP Negeri 3 Pelalawan, Pelalawan Regency. This study uses a qualitative approach with phenomenological methods. Based on the results of the analysis and discussion, it is concluded that the obstacles that occur in the implementation of learning Indonesian are as follows: first, the network is less stable; second, the learning atmosphere is not comfortable because many friends are noisy because the network is not good; third, learning videos are intermittent; fourth, in providing material via whatsapp so that it does not include learning objectives, students do not understand the previous material; fifth, students are late to enter the zoom application because they have to find a network to the forest or the pier. In addition, there are students who do not have cellphones, so they have to wait for their parents to come home from work before they can communicate with the teacher; and Sixth, the internet quota that runs out during the closing learning implementation, if the electricity goes out, the internet network will disappear.